2023
DOI: 10.3390/app13148526
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Classification of High-Resolution Satellite Images for Mangrove Mapping

Abstract: Detailed information about mangroves is crucial for ecological and environmental protection and sustainable development. It is difficult to capture small patches of mangroves from satellite images with relatively low to medium resolution. In this study, high-resolution (0.8–2 m) images from Chinese GaoFen (GF) and ZiYuan (ZY) series satellites were used to map the distribution of mangroves in coastal areas of Guangdong Province, China. A deep-learning network, U2-Net, with attention gates was applied to extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Some studies have shown promising results in binary classification in which mangrove are distinguished from non-mangrove classes such as water, human settlement, and agricultural field [28,29]. However, this study identified multiple classes of intricate mangrove regions that contributed detailed LULC information for the management of mangroves.…”
Section: Complexity Of Land Use Compared To Land Covermentioning
confidence: 90%
See 1 more Smart Citation
“…Some studies have shown promising results in binary classification in which mangrove are distinguished from non-mangrove classes such as water, human settlement, and agricultural field [28,29]. However, this study identified multiple classes of intricate mangrove regions that contributed detailed LULC information for the management of mangroves.…”
Section: Complexity Of Land Use Compared To Land Covermentioning
confidence: 90%
“…Among state-of-the-art models, the U-Net segmentation model and artificial neural networks (ANNs) have consistently demonstrated superior performance in remote sensing image analysis [25][26][27]. However, limited studies have applied the U-Net and ANN models using different spatial resolution of satellite images for mangrove ecosystem [28][29][30]. Moreover, their research focused only on mangrove and non-mangrove classifications to highlight the distribution and dynamics of mangroves.…”
Section: Introductionmentioning
confidence: 99%